National income and flow of funds analysis - Powelson, John P. (New York : McGraw-Hill Book Company, Inc., 1960)
This is a textbook for a course in national income. It is intended both to teach the accounts themselves and to cover techniques of analyzing them
Includes bibliographical footnotes and index.
osa; 27/11/18
Loans
Keywords: National account; Flow of fund; Income